HPAI H5N1 in Europe 2007: Poultry and Wild Birds - Burgos, Sigfrido; Burgos, Sergio A. (International Journal of Poultry Science, 2007)
There were 308 HPAI cases in wild birds, most of them in Germany and 13 HPAI outbreaks in poultry, with clear spatial and temporal infectious patterns. Grebes, swans, ducks, chickens and turkeys got most frequently infected. The United Kingdom, Czech Republic and Germany hosted many viral incursions.